Exploring interdependencies, vulnerabilities, gaps and bridges in care transitions of patients with complex care needs using the Functional Resonance Analysis Method - Ann-Therese Hedqvist; Gesa Praetorius; Mirjam Ekstedt (BMC, 2023)
Abstract Background Hospital discharge is a complex process encompassing multiple interactions and requiring coordination. To identify potential improvement measures in care transitions for people with complex care needs, intra- and inter-organisational everyday work needs to be properly understood, including its interdependencies, vulnerabilities and gaps. The aims of this study were to 1) map coordination and team collaboration across healthcare and social care organisations, 2) describe interdependencies and system variability in the discharge process for older people with complex care needs, and 3) evaluate the alignment between discharge planning and the needs in the home. Methods Data were collected through participant observations, interviews, and document review in a region of southern Sweden. The Functional Resonance Analysis Method (FRAM) was used to model the discharge process and visualise and analyse coordination of care across healthcare and social care organisations. Results Hospital discharge is a time-sensitive process with numerous couplings and interdependencies where healthcare professionals' performance is constrained by system design and organisational boundaries. The greatest vulnerability can be found when the patient arrives at home, as maladaptation earlier in the care chain can lead to an accumulation of issues for the municipal personnel in health and social care working closest to the patient. The possibilities for the personnel to adapt are limited, especially at certain times of day, pushing them to make trade-offs to ensure patient safety. Flexibility and appropriate resources enable for handling variability and responding to uncertainties in care after discharge. Conclusions Mapping hospital discharge using the FRAM reveals couplings and interdependencies between various individuals, teams, and organisations and the most vulnerable point, when the patient arrives at home. Resilient performance in responding to unexpected events and variations during the first days after the return home requires a system allowing flexibility and facilitating successful adaptation of discharge planning.